Low apolipoprotein B and LDL-cholesterol are associated with the risk of cardiovascular and all-cause mortality: a prospective cohort - Xiaolin Yu; Yujuan Yuan; Xiangyu Dong; Zulipiyemu Xier; Ling Ma; Hui Peng; Guoqing Li; Yining Yang (Annals of Medicine, 2025)
Background The association between low-density lipoprotein (LDL) cholesterol and increased mortality risk has been well-documented, yet apolipoprotein B (apoB) is regarded as a more precise risk indicator. However, a comprehensive analysis integrating both markers in relation to mortality risk remains unreported.Objectives This study aimed to investigate the relationship between LDL cholesterol levels and mortality across varying apoB concentrations within the general population.Methods Data from 15,380 participants in the 2005–2016 National Health and Nutrition Examination Survey (NHANES) were utilized to construct Cox regression models and apply restricted cubic splines, assessing the association between LDL cholesterol and mortality across distinct apoB stratifications.Results The study cohort had a median (IQR) age of 46.0 (32.0, 60.0) years, with 7949 (51.8%) males. During a median follow-up of 101.0 months (IQR: 67–137), 1771 (8.8%) all-cause mortality events were observed; 443 (2.1%) deaths were attributed to cardiovascular diseases, while 109 (0.5%) resulted from cerebrovascular diseases. Low apoB and LDL-cholesterol levels were independently linked to an elevated risk of all-cause and cardiovascular mortality. Compared with participants having apoB <90 mg/dL and LDL-cholesterol levels between 100–129 mg/dL, those with LDL-cholesterol <70 mg/dL (HR, 1.81; 95%CI: 1.39–2.36) and 70–99 mg/dL (HR, 1.28; 95%CI: 1.01–1.62) demonstrated a higher risk of all-cause mortality. Additionally, reduced apoB levels contributed to an increased risk of cardiovascular mortality among individuals with low LDL-cholesterol levels.Conclusions Low apoB and LDL-cholesterol levels were associated with heightened all-cause and cardiovascular mortality risk in the general population. Conversely, high apoB and low LDL-cholesterol levels did not correlate with increased mortality risk.